Sister Wendy's story of painting the age of revolution ([London] BBC Video, 1996)
Sister Wendy Beckett looks at the two cataclysms that shook art to its foundations : The industrial revolution and the French revolution.
VHS format.
Keywords: Painting, European; Painting, Modern -- 17th century